Polyethylene-like degradable copolyester as well as preparation method and application thereof
Through the oxalic acid short-chain oligopolymer-assisted polycondensation method, the problem of difficult growth of the molecular weight of polyethylene-like polyester during the polycondensation process is solved, and the high molecular weight growth and controllable degradation effect of polyethylene-like degradable copolyester is achieved, effectively controlling plastic pollution.
Patent Information
- Application Number
- CN202411836661.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing polyethylene-like polyester is difficult to achieve high molecular weight during the polycondensation process, and the oxalic acid structure has poor thermal stability at high temperatures, making it difficult to react with long-chain dibasic acid or its esterides to form high molecular weight PE-like polyester.
By using the method of assisted polycondensation of oxalic acid short-chain oligomers, polyethylene-like degradable copolyesters with a main chain containing long-chain methylene structure and oxalate bonds were prepared.
The high molecular weight growth of polyethylene-like degradable copolyester has been achieved, its mechanical properties and crystallization capabilities have been optimized, and the controllable degradation effect has been achieved by regulating the length of methylene and the number of oxalic acid unit structures has been achieved, effectively controlling plastic pollution.
Smart Images

Figure CN119661818A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material synthesis, and in particular to a polyethylene (PE)-like degradable copolyester and a preparation method and application thereof. Background Art
[0002] The production capacity of ethylene is an important indicator of a country's petrochemical development level. As of 2021, the world's production of polyethylene (PE) is 120 million tons, accounting for 1 / 4 of the total plastic production. Polyethylene is widely used in electronics, military industry, agriculture, construction and aviation due to its odorlessness, good low temperature resistance, high gas barrier properties and good chemical stability. However, it also has the disadvantages of poor mechanical properties, poor heat resistance, low surface hardness and extremely slow degradation rate or even no degradation. With the introduction of the "Plastic Restriction Order" and the "Plastic Ban Order", the management measures to deal with plastic pollution have been further upgraded. Making PE degradable is one of the important measures to solve the "white pollution" under the plastic ban order.
[0003] PE-like polyester is a polyester containing long-chain methylene groups formed by polymerization of long-chain dibasic acids and long-chain diols. Compared with the conventional short-chain polyester structure, the ester bond density is significantly reduced. The long-chain methylene structure enables it to have similar crystallization ability and water-blocking properties as PE. However, during the polycondensation process, the long-chain diol has a high boiling point and is not easy to remove, resulting in the inability to increase the molecular weight. In addition, the feed requirement strictly controls the alcohol-acid ratio to 1, which makes the synthesis conditions and ingredient control of PE-like polyesters very demanding. Although PE-like polyesters introduce hydrolyzable ester bonds into their structure, they are still hydrophobic materials. It is difficult for ester bonds to undergo nucleophilic substitution reactions with water and then degrade. Therefore, the hydrolysis and composting degradation of PE-like polyesters are still very slow.
[0004] Polyoxalate is a highly hydrophilic polyester, a new type of polyester material that can truly achieve full natural degradation. If the oxalic acid structure can be introduced into the PE-like polyester material, a PE-like degradable polyester material with adjustable degradation rate can be achieved. However, oxalic acid or dimethyl oxalate or diethyl oxalate has poor thermal stability and is difficult to maintain stability during the high-temperature melt polycondensation process, and is unable to react with long-chain dibasic acids and long-chain diols to form high-molecular-weight PE-like polyesters. Therefore, how to introduce oxalic acid structures into PE-like polyesters to achieve regulation of degradation rates, how to improve the stability of oxalic acid monomers to ensure that they do not decompose during polycondensation with long-chain dibasic acids or their esters, and promote the growth of the molecular weight of PE-like polyesters, have become key challenges in the synthesis of PE-like degradable polyesters. Summary of the invention
[0005] The main purpose of the present invention is to provide a polyethylene (PE)-like degradable copolyester and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0006] Another object of the present invention is to provide applications of the polyethylene-like degradable copolyester.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0008] The embodiment of the present invention provides a polyethylene-like degradable copolyester, the structural formula of which is shown in formula (1):
[0009]
[0010] Wherein, -R1- is a structural unit of a long-chain dibasic acid or its ester, -O-R2-O- is a structural unit of a long-chain diol, m, n, and x are all integers, m=1 to 10, n=1 to 10, and x=10 to 100; and -R1- and The molar ratio is 3:2 to 19:1.
[0011] In some embodiments, the structural unit of the long-chain dibasic acid or its ester is selected from at least one of the structures shown in formula (2):
[0012]
[0013] Here, a is an integer, a=10~23.
[0014] In some embodiments, the long-chain diol is selected from at least one of the structures shown in formula (3):
[0015]
[0016] Wherein, c is an integer, c=12~25.
[0017] The embodiment of the present invention also provides a method for preparing a polyethylene-like degradable copolyester, which comprises:
[0018] Mixing dimethyl oxalate and / or diethyl oxalate, a first diol and an esterification catalyst to form a first mixed system, subjecting the first mixed system to a first esterification reaction or a first transesterification reaction to obtain a first esterification product or a first transesterification product; then cooling the system to perform a first pre-polycondensation reaction to obtain an oxalic acid prepolymer with a low degree of polymerization;
[0019] Mixing a long-chain dibasic acid or an esterified product thereof, a long-chain diol, and an esterification catalyst to form a second mixed system, and subjecting the second mixed system to a second esterification reaction or a second transesterification reaction to obtain a second esterification product or a second transesterification product;
[0020] The oxalic acid prepolymer, the second esterification product or the second ester exchange product are mixed to form a third mixed system, and the third mixed system is subjected to a third ester exchange reaction under the condition that the melt is completely melted, and then the temperature is increased to carry out a second pre-polycondensation reaction and a final polycondensation reaction to obtain a polyethylene-like degradable copolyester.
[0021] The embodiment of the present invention also provides a polyethylene-like degradable copolyester prepared by the above-mentioned preparation method.
[0022] The embodiments of the present invention also provide the use of the aforementioned polyethylene-like degradable copolyester in the fields of preparing agricultural mulch films, fiber fabrics, telecommunication cables, packaging materials, plastic container products, tissue engineering scaffolds or drug carriers.
[0023] Compared with the prior art, the present invention has the following beneficial technical effects:
[0024] The present invention adopts a method of assisting condensation polymerization with short-chain oxalic acid oligomers to solve the problem that long-chain diol condensation polymerization is difficult to remove, and the oxalic acid content is precisely regulated. The main chain of the obtained polyethylene-like degradable copolyester contains a long-chain methylene structure and an oxalate bond, which not only has excellent mechanical properties and crystallization ability, but also can achieve controllable degradation of the polyethylene-like polyester by regulating the methylene length and the number of oxalic acid unit structures. It can effectively control the problem of plastic pollution, can be widely used in plastic products, and meet the requirements of different application scenarios for the stability and degradation rate of degradable materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a H-NMR spectrum curve of the polyethylene-like degradable polyester prepared in Example 1 of the present invention;
[0027] Figure 2 This is a DSC curve diagram of the polyethylene-like degradable polyester prepared in Example 1 of the present invention;
[0028] Figure 3 This is a stress-strain curve of the polyethylene-like degradable polyester prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The main method is to use the method of auxiliary polycondensation of short-chain oxalic acid oligomers to solve the problem that long-chain diol polycondensation is difficult to remove, and accurately control the oxalic acid content. The main chain containing long-chain methylene structure and oxalate bond not only has excellent mechanical properties and crystallization ability, but also can achieve controllable degradation of controllable polyethylene polyester by regulating the content of oxalic acid structure. The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The technical solution, its implementation process and principle will be further explained as follows.
[0031] Specifically, as one aspect of the technical solution of the present invention, the structural formula of the polyethylene (PE)-like degradable copolyester involved is shown in formula (1):
[0032]
[0033] Among them, -R1- is a structural unit of a long-chain dibasic acid or its ester, -O-R2-O- is a structural unit of a long-chain diol, m, n, and x are all integers, m=1-10, n=1-10, and x=10-100.
[0034] In some embodiments, -R1- is The molar ratio is 3:2 to 19:1, preferably 4:1 to 19:1.
[0035] In some embodiments, the structural unit of the long-chain dibasic acid or its ester is selected from at least one of the structures shown in formula (2):
[0036]
[0037] Wherein, a is an integer, and a=10 to 23. Furthermore, the value of a is preferably an even number, for example, a may be preferably 10, 12, 14, 16, 18, 20, 22, and the like.
[0038] In some embodiments, the long-chain diol is selected from at least one of the structures shown in formula (3):
[0039]
[0040]
[0041] Wherein, c is an integer, and c=12 to 25. Furthermore, the value of c is preferably an even number, for example, c may be preferably 12, 14, 16, 18, 20, 22, 24, and the like.
[0042] Furthermore, the polyethylene-like degradable copolyester provided by the present invention preferentially selects even-numbered long-chain diacids or their esters and even-numbered long-chain diols to ensure stable comprehensive thermodynamic properties and excellent crystallization ability and barrier properties. In addition, the present invention introduces oxalic acid segments into the main chain of the polyethylene-like degradable copolyester through molecular chain structure design to improve its hydrophilicity and degradation ability, increase the biocompatibility of the polyethylene-like degradable copolyester, and expand its application fields from agricultural mulch, fiber fabrics, telecommunication cables, packaging materials, plastic container products to tissue engineering scaffolds, drug carriers, and sustained release, showing broad application prospects.
[0043] In some embodiments, the polyethylene-like degradable copolyester backbone The structure is introduced by auxiliary polycondensation, and the structural unit of the auxiliary polycondensation raw material oxalic acid prepolymer is selected from at least one of the structures of formula (4):
[0044]
[0045] in, The diol derived from dimethyl oxalate or diethyl oxalate, -O-R3-O- is selected from at least one of ethylene glycol, propylene glycol and butanediol; b is an integer, b=1-10.
[0046] In some embodiments, the intrinsic viscosity of the PE-like degradable copolyester is 1.5-2.5 dL / g, and the number average molecular weight is 80,000-160,000 g / mol; according to the L*a*b* color model, the L* value is greater than 80, the absolute value of a* is less than 4, and the absolute value of b* is less than 8.
[0047] In some embodiments, the PE-like degradable copolyester has a glass transition temperature of -80 to 65°C, a melting point of 70 to 105°C, a tensile strength of 10 to 40 MPa, an elongation at break of 600 to 1600%, and a water vapor permeability of 4×10 -14 ~10×10 -14 g cm / cm 2 ·s·Pa, the mass loss after 60 days of hydrolysis is 30-50%, the mass loss after 60 days of enzyme degradation is 40-70%, and the mass loss after 60 days of seawater degradation is 5-15%.
[0048] In summary, the polyethylene-like degradable copolyester can exhibit excellent thermal and mechanical properties, and the degradation rate can be regulated by the methylene length and the number of oxalic acid units. It can effectively address the problem of plastic pollution and meet the degradation rate requirements of different application scenarios.
[0049] As another aspect of the technical solution of the present invention, it relates to a method for preparing a polyethylene-like degradable copolyester, which comprises:
[0050] Mixing dimethyl oxalate and / or diethyl oxalate, a first diol and an esterification catalyst to form a first mixed system, subjecting the first mixed system to a first esterification reaction or a first transesterification reaction to obtain a first esterification product or a first transesterification product; then cooling the system to perform a first pre-polycondensation reaction to obtain an oxalic acid prepolymer with a low degree of polymerization;
[0051] Mixing a long-chain dibasic acid or an esterified product thereof, a long-chain diol, and an esterification catalyst to form a second mixed system, and subjecting the second mixed system to a second esterification reaction or a second transesterification reaction to obtain a second esterification product or a second transesterification product;
[0052] The oxalic acid prepolymer, the second esterification product or the second ester exchange product are mixed to form a third mixed system, and the third mixed system is subjected to a third ester exchange reaction under the condition that the melt is completely melted, and then the temperature is increased to carry out a second pre-polycondensation reaction and a final polycondensation reaction to obtain a polyethylene-like degradable copolyester.
[0053] In some embodiments, the first diol includes at least one of short-chain diols such as ethylene glycol, propylene glycol, and butanediol, but is not limited thereto.
[0054] In some embodiments, the molar ratio of the dimethyl oxalate and / or diethyl oxalate to the first diol (ethylene glycol or propylene glycol or butylene glycol) is 1:1.2 to 1:1.5.
[0055] In some embodiments, the temperature of the first esterification reaction or the first transesterification reaction is 140 to 180° C., preferably 140 to 160° C., and the time is 1 to 4 hours, preferably 2 to 4 hours.
[0056] In some embodiments, the polyethylene-like degradable copolyester backbone The structure is introduced by an auxiliary polycondensation method, and the auxiliary polycondensation raw material oxalic acid prepolymer has at least one of the structures shown in formula (4):
[0057]
[0058] In the structure of formula (4), The diol derived from dimethyl oxalate or diethyl oxalate, the -O-R3-O- source is selected from at least one of ethylene glycol, propylene glycol, butanediol, etc., with ethylene glycol and butanediol being preferred; b is an integer, b=1-10.
[0059] In some embodiments, the preparation method includes: after the first esterification reaction or the first ester exchange reaction is completed, the temperature is reduced to 100-150°C, and the pressure of the reaction system is reduced to 200-1000 Pa to carry out a first pre-condensation reaction for 0.5-4 hours to obtain an oxalic acid prepolymer with a low degree of polymerization.
[0060] In some more specific embodiments, the preparation method comprises:
[0061] Dimethyl oxalate or diethyl oxalate, ethylene glycol or propylene glycol or butylene glycol and an esterification catalyst are mixed to form a first mixed system, and the first mixed system is subjected to a first esterification reaction or a first transesterification reaction at 140-180° C., and the time from the first drop of methanol or ethanol dripping is the timing zero point to the time when the amount of byproduct methanol or ethanol collected is more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction;
[0062] The product of the above step is cooled to 110-150° C., and the reaction system is depressurized to 200-1000 Pa to carry out a first pre-polycondensation reaction, with a polycondensation time of 0.5-4 hours to obtain an oxalic acid prepolymer with a low degree of polymerization.
[0063] In some more specific embodiments, the preparation method includes: after the first esterification reaction or the first ester exchange reaction is completed, the temperature is reduced to 110-130°C, and the pressure of the reaction system is reduced to 200-400 Pa to carry out a first pre-condensation reaction for 1-1.5 hours to obtain an oxalic acid prepolymer with a low degree of polymerization.
[0064] In some embodiments, the molar ratio of the sum of the molar amount of the long-chain dibasic acid or its long-chain dibasic acid ester and the molar amount of the oxalate structure in the oxalic acid prepolymer to the long-chain diol is 1:1 to 1.2:1.
[0065] In some embodiments, the structure of the long-chain dibasic acid or its ester, and the structure of the long-chain diol are as described above and will not be repeated here.
[0066] In some embodiments, the temperature of the second esterification reaction or the second transesterification reaction is 170-210° C., preferably 170-190° C., and the time is 1-4 h, preferably 2-4 h.
[0067] In some embodiments, the mass fraction of the long-chain dibasic acid or its ester in the second mixed system is 0.1‰ to 3‰, preferably 0.5‰ to 1‰.
[0068] In some more specific embodiments, the preparation method includes: mixing a long-chain dibasic acid or its esterification product, a long-chain diol and an esterification catalyst to form a second mixed system, and performing a second esterification reaction or a second ester exchange reaction on the second mixed system at 170-210°C, with the first drop of methanol or water dripping as the timing zero point and the esterification reaction or ester exchange reaction endpoint being when the amount of by-product methanol or water collected is more than 95% of the theoretical value.
[0069] In some embodiments, the esterification catalyst used in the first mixed system and the second mixed system includes at least one of an antimony-based catalyst, a titanium-based catalyst, etc. For example, the antimony-based catalyst can be preferably selected from any one or a combination of two or more of antimony trioxide, antimony acetate, antimony glycol, triethyl antimonate, etc.; the titanium-based catalyst can be preferably selected from any one or a combination of two or more of titanium isopropoxide, tetrabutyl titanate, tetraethyl titanate, etc., but is not limited thereto.
[0070] In some more specific embodiments, in the first mixed system, the mass of the esterification catalyst accounts for 0.1‰ to 3‰ of the mass of dimethyl oxalate and / or diethyl oxalate, preferably 0.5‰ to 1‰.
[0071] In some more specific embodiments, in the second mixed system, the mass of the esterification catalyst accounts for 0.1‰ to 3‰ of the mass of the long-chain dibasic acid or its esterified substance, and preferably 0.5‰ to 1‰.
[0072] In some embodiments, the temperature of the third transesterification reaction is 130-160° C., preferably 140-150° C., and the time is 0.5-2 h, preferably 1-1.5 h.
[0073] In some embodiments, the preparation method includes: gradually heating the reaction system obtained by the third ester exchange reaction to 190-240°C, reducing the pressure of the reaction system to 100-500Pa for a second pre-polycondensation reaction, and the time of the second pre-polycondensation reaction is 0.5-3h; then reducing the pressure of the reaction system to less than 20Pa for a final polycondensation reaction, the stable vacuum degree of the final polycondensation reaction does not exceed 7Pa, and the time of the final polycondensation reaction is 0.5-2h, to obtain the polyethylene-like degradable copolyester.
[0074] In some preferred embodiments, the preparation method specifically comprises:
[0075] The oxalic acid prepolymer prepared above, the second esterification product or the second transesterification product are mixed to form a third mixed system, and the third mixed system is subjected to a third transesterification reaction under the condition that the melt is completely melted at 130 to 160° C., and the reaction time is 0.5 to 2 hours;
[0076] The reaction system obtained by the third ester exchange reaction is gradually heated to 190-240°C, and the reaction system is depressurized to 100-500Pa for a second pre-polycondensation reaction, and the second pre-polycondensation reaction time is 0.5-3h; the reaction system is further depressurized to less than 20Pa for a final polycondensation reaction, and the stable vacuum degree of the final polycondensation reaction is less than or equal to 7Pa, and the final polycondensation reaction time is 0.5-2h to obtain the polyethylene-like degradable copolyester.
[0077] In some more preferred embodiments, the preparation method includes: gradually heating the reaction system obtained by the third ester exchange reaction to 200-220°C, reducing the pressure of the reaction system to 200-400Pa for a second pre-polycondensation reaction, and the time of the second pre-polycondensation reaction is 1-1.5h; then reducing the pressure of the reaction system to less than 20Pa for a final polycondensation reaction, the stable vacuum degree of the final polycondensation reaction does not exceed 7Pa, and the time of the final polycondensation reaction is 1-2h, to obtain the polyethylene-like degradable copolyester.
[0078] Among them, in some more preferred embodiments, the preparation method of the polyethylene (PE)-like degradable copolyester of the present invention specifically comprises the following steps:
[0079] Step 1, dimethyl oxalate or diethyl oxalate, ethylene glycol or propylene glycol or butylene glycol and an esterification catalyst are mixed to form a first mixed system, wherein the first mixed system is subjected to a first transesterification reaction or a first transesterification reaction at 140 to 180° C., preferably 140 to 160° C., and the first drop of methanol or ethanol is used as the timing zero point, and the esterification reaction or transesterification reaction end point is when the amount of byproduct methanol or ethanol collected is more than 95% of the theoretical value;
[0080] Step 2, cooling the product of step 1 to 100-150° C., preferably 110-130° C., reducing the pressure of the reaction system to 200-1000 Pa, preferably 200-400 Pa, to carry out a first pre-polycondensation reaction, the time of the first pre-polycondensation reaction is 0.5-4 h, preferably 1-1.5 h, to obtain an oxalic acid prepolymer with a low degree of polymerization;
[0081] The low-polymerization degree oxalic acid prepolymer obtained by the first pre-polycondensation reaction in step 2 of the present invention can significantly increase the thermal decomposition temperature of dimethyl oxalate or diethyl oxalate, ensuring that it does not decompose during the melt polycondensation reaction with the long-chain dibasic acid or its ester and the long-chain diol;
[0082] Step 3, mixing a long-chain dibasic acid or its esterified product, a long-chain diol and an esterification catalyst to form a second mixed system, wherein the second mixed system is subjected to a second esterification reaction or a second transesterification reaction at 170 to 210° C., preferably 170 to 190° C., and the time from the first drop of methanol or water dripping is the timing zero point to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol or water collected is more than 95% of the theoretical value;
[0083] Step 4, mixing the oxalic acid prepolymer obtained in step 2 and the product of step 3 to form a third mixed system, wherein the third mixed system is subjected to a third transesterification reaction at 130 to 160° C., preferably 140 to 150° C., under the condition that the melt is completely melted, and the third transesterification reaction time is 0.5 to 2 hours, preferably 1 to 1.5 hours;
[0084] In step 4 of the present invention, the oxalic acid prepolymer is fully transesterified with the long-chain dibasic acid or its esterification product and the long-chain diol, and the ethylene glycol, propylene glycol or butanediol structural units in the oxalic acid prepolymer can be almost completely transesterified into long-chain diols, and the ethylene glycol, propylene glycol or butanediol structural units are completely extracted from the polymerization system during the pre-polycondensation process;
[0085] Step 5, gradually heating the reaction system of step 4 to 190-240°C, preferably 200-220°C, reducing the pressure of the reaction system to 100-500Pa, preferably 200-400Pa, for a second pre-polycondensation reaction, the time of the second pre-polycondensation reaction is 0.5-3h, preferably 1-1.5h; the reaction system is further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction has a stable vacuum degree of less than or equal to 7Pa, and the final polycondensation time is 0.5-2h, preferably 1-2h, to obtain the polyethylene (PE)-like degradable copolyester.
[0086] In summary, in the preparation method of the present invention, the initial thermal decomposition temperature (reaching 5% mass loss) of the low-polymerization degree oxalic acid prepolymer synthesized first reaches 240°C, which effectively solves the problem of thermal degradation of dimethyl oxalate (initial thermal decomposition temperature 165°C) and diethyl oxalate (initial thermal decomposition temperature 185°C) during melt polycondensation with long-chain dibasic acid or its esterification product and long-chain diol; on the other hand, the oxalic acid prepolymer adopts diols with lower boiling points such as ethylene glycol, propylene glycol or butanediol, and undergoes sufficient ester exchange reaction during the mixing process with long-chain dibasic acid or its esterification product and long-chain diol, and the low-boiling diol is extracted from the polymerization system during the polycondensation process. When the addition amount of the oxalic acid prepolymer is less than 20%, the low-boiling diol in the oxalic acid prepolymer can be completely extracted from the polymerization system to ensure the integrity of the polyethylene-like polyester structure, and the molecular weight is increased by shortening the reaction time without the need to add a polycondensation catalyst, thereby reducing the burden of the metal catalyst on the environment.
[0087] In addition, the oxalic acid prepolymer-assisted condensation method provides a new polymerization idea for the synthesis of high molecular weight polyethylene polyesters. At the same time, it controls the degradation rate by changing the content of oxalic acid structure in the molecular chain. It can be widely used in plastic products, effectively control plastic pollution problems, and meet the requirements of different application scenarios for the stability and degradation rate of degradable materials.
[0088] As another aspect of the technical solution of the present invention, it relates to a polyethylene-like degradable copolyester prepared by the above method.
[0089] As another aspect of the technical solution of the present invention, it also relates to the application of the polyethylene-like degradable copolyester in the preparation of agricultural mulch films, fiber fabrics, telecommunication cables, packaging materials, plastic container products, tissue engineering scaffolds or drug carriers.
[0090] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0091] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0092] In the embodiment, a differential scanning calorimeter (Mettler Toledo DSC) is used to perform thermal performance testing, wherein the heating rate is 10° C. / min, the temperature range is -80° C.-200° C., and the measurement is performed in a N 2 atmosphere.
[0093] In the embodiment, a Zwicki 1kN universal material testing machine is used to perform mechanical property testing, wherein the sample strip has a length of 15.0 mm, a width of 2.0 mm, a thickness of 1.0 mm, and a tensile speed of 20 mm / min.
[0094] In the embodiment, Labthink W3-006 was used to test the water vapor barrier performance. The test was conducted by measuring the difference in the evaporation of water vapor before and after the test at a temperature of 38°C and a humidity of 90% RH. The sample permeation area was 33 cm 2 .
[0095] In the embodiment, a phosphate buffer solution is used as a degradation solvent, and a hydrolysis degradation test is performed at a constant temperature of 37° C., wherein the sample is 10 mm in length, 10 mm in width, and 0.5 mm in thickness.
[0096] In the example, a phosphate buffer solution containing 0.1 mg / ml lipase was used as a degradation solvent, and an enzyme degradation test was performed at a constant temperature of 37° C., wherein the sample was 10 mm in length, 10 mm in width, and 0.5 mm in thickness.
[0097] In the embodiment, 35 g of sea salt is used to calibrate in a 1 L volumetric flask, and the seawater degradation test is carried out at a constant temperature of 37° C., wherein the sample is 10 mm in length, 10 mm in width, and 0.5 mm in thickness.
[0098] Example 1
[0099] 0.063 mol of dimethyl oxalate, 0.088 mol of ethylene glycol and 0.5‰ (based on the mass fraction of dimethyl oxalate) of titanium isopropoxide are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of methanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 100°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0100] 0.237 mol of dimethyl dodecanedioate, 0.32 mol of 1,12-dodecanediol and tetrabutyl titanate with a mass fraction of 1‰ (accounting for dimethyl dodecanedioate) are put into a reactor, and under the protection of nitrogen, the temperature is gradually raised to 180°C for a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol or water dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 150°C, and the oxalic acid ethylene glycol prepolymer prepared in the first step is added to carry out a third transesterification reaction, and the reaction is carried out for 1 hour;
[0101] The system was gradually heated to 210°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 2h, and a light yellow PE-like degradable copolyester was obtained.
[0102] The main chain double bond-containing degradable copolyester prepared in this example was subjected to H NMR spectrum, DSC, mechanical properties, water vapor barrier properties and degradation performance tests.
[0103] Figure 1 , Figure 2 , Figure 3 The following are the H NMR spectrum, DSC curve and stress-strain curve of the PE-like degradable polyester prepared in this embodiment. Figure 1It can be seen that the molecular structure of the biodegradable polyester is clear. In the dibasic acid composition, the molar ratio of dodecanedioic acid to oxalic acid is 80.2:19.8, and the residual amount of ethylene glycol is 0.8%, which can be ignored. Figure 2 It can be seen that the glass transition temperature of the degradable polyester is -66.8°C and the melting point is 79.0°C. Figure 3 It can be seen that the tensile strength of the biodegradable polyester is 17.4 MPa and the elongation at break is 981%.
[0104] After testing, the intrinsic viscosity of this type of PE degradable copolyester is 1.54 dL / g; the number average molecular weight is 87000 g / mol; according to the L*a*b* color model, the L* value is 85, the a* value is 3.5, and the b* value is 7.3.
[0105] The water vapor permeability coefficient of this type of PE degradable copolyester is 9.31×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 65%, the mass loss due to hydrolysis within 60 days was 46%, and the mass loss due to seawater degradation within 60 days was 11%.
[0106] Example 2
[0107] 0.033 mol of dimethyl oxalate, 0.046 mol of propylene glycol and a composite catalyst of tetrabutyl titanate and triethyl antimonate with a mass fraction of 0.5‰ (based on dimethyl oxalate) are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1.5 hours, from the first drop of methanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 120°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree propylene glycol oxalate prepolymer;
[0108] 0.267 mol of dimethyl tridecanedioate, 0.31 mol of 1,13-tridecanediol and a composite catalyst of tetrabutyl titanate and ethylene glycol titanium with a mass fraction of 0.6‰ (based on dimethyl tridecanedioate) are put into a reactor, and the temperature is gradually raised to 180°C under nitrogen protection for a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol or water is regarded as zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is regarded as the end point of the esterification reaction or transesterification reaction; the system is cooled to 155°C, and the propylene glycol oxalate prepolymer prepared in the first step is added to carry out a third transesterification reaction, and the reaction is carried out for 1.5 hours;
[0109] The system was gradually heated to 200°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1.5h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1.5h, and a milky white PE-like degradable copolyester was obtained.
[0110] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 90.1:9.9, the residual amount of ethylene glycol is 0.4% which can be ignored; the intrinsic viscosity is 1.64dL / g; the number average molecular weight is 120000g / mol; according to the L*a*b* color model, the L* value is 87, the a* value is 3.2, and the b* value is 6.4; the glass transition temperature is -68.3℃, the melting point is 76.8℃; the tensile strength is 16.9MPa, the elongation at break is 900%; the water vapor permeability coefficient is 7.62×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 63%, the mass loss due to hydrolysis within 60 days was 42%, and the mass loss due to seawater degradation within 60 days was 10%.
[0111] Example 3
[0112] 0.018 mol of dimethyl oxalate, 0.025 mol of butanediol and 0.5‰ (based on the mass fraction of dimethyl oxalate) of titanium isopropoxide are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of methanol or ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 125°C, the reaction system is depressurized to 400 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree butanediol oxalate prepolymer;
[0113] 0.282 mol of dimethyl dodecanedioate, 0.32 mol of 1,12-dodecanediol and tetrabutyl titanate with a mass fraction of 0.8‰ (accounting for dimethyl dodecanedioate) are put into a reactor, and the temperature is gradually raised to 180°C under nitrogen protection to carry out a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 155°C, and the oxalic acid butanediol ester prepolymer prepared in the first step is added to carry out a third transesterification reaction under the condition that the melt is completely melted, and the reaction is carried out for 1 hour;
[0114] The system was gradually heated to 210°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1 hour; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1 hour, and a milky white PE-like degradable copolyester was obtained.
[0115] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 95:5, the residual amount of ethylene glycol is 0.2% which can be ignored; the intrinsic viscosity is 1.94dL / g; the number average molecular weight is 138000g / mol; according to the L*a*b* color model, the L* value is 84, the a* value is 2.9, and the b* value is 4.8; the glass transition temperature is -67.4℃, the melting point is 82.3℃; the tensile strength is 13.2MPa, the elongation at break is 1130%; the water vapor permeability coefficient is 4.92×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 52%, the mass loss due to hydrolysis within 60 days was 37%, and the mass loss due to seawater degradation within 60 days was 8%.
[0116] Example 4
[0117] 0.033 mol of dimethyl oxalate, 0.046 mol of ethylene glycol and antimony trioxide with a mass fraction of 0.6‰ (based on dimethyl oxalate) are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of methanol or ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 125°C, the reaction system is depressurized to 300 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0118] 0.267 mol of dimethyl octadecane dioate, 0.31 mol of 1,18-octadecane diol and 0.6‰ (based on the mass fraction of dimethyl octadecane dioate) of tetrabutyl titanate are put into a reactor, and under the protection of nitrogen, the temperature is gradually raised to 190°C for a second esterification reaction or transesterification reaction, and the reaction is carried out for 1 hour. The time is zero when the first drop of methanol drips, and the end point of the esterification reaction or transesterification reaction is when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 150°C, and the oxalic acid glycol prepolymer prepared in the first step is added to carry out a third transesterification reaction, and the reaction is carried out for 1.5 hours;
[0119] The system was gradually heated to 190°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time being 1h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1h, and a milky white PE-like degradable copolyester was obtained.
[0120] According to the test, the molar ratio of octadecane dioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 90.2:9.8, the residual amount of ethylene glycol is 0.5% which can be ignored; the intrinsic viscosity is 2.31dL / g; the number average molecular weight is 148000g / mol; according to the L*a*b* color model, the L* value is 84, the a* value is 2.9, and the b* value is 5.3; the glass transition temperature is -67.2℃, the melting point is 84.7℃; the tensile strength is 14.8MPa, the elongation at break is 850%; the water vapor permeability coefficient is 8.94×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 59%, the mass loss due to hydrolysis within 60 days was 46%, and the mass loss due to seawater degradation within 60 days was 12%.
[0121] Example 5
[0122] 0.033 mol of dimethyl oxalate, 0.046 mol of ethylene glycol and antimony acetate with a mass fraction of 0.7‰ (ε dimethyl oxalate) are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of methanol or ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 125°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0123] 0.267 mol of dimethyl eicosanedioate, 0.31 mol of 1,20-eicosanedioate and 0.6‰ (based on the mass fraction of dimethyl eicosanedioate) of triethyl antimonate are put into a reactor, and under the protection of nitrogen, the temperature is gradually raised to 185° C. for a second esterification reaction or transesterification reaction, and the reaction is carried out for 1 hour. The time from the first drop of methanol dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 155° C., and the oxalic acid glycol prepolymer prepared in the first step is added to carry out a third transesterification reaction, and the reaction is carried out for 1.5 hours;
[0124] The system was gradually heated to 195°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1.5h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1h, and a milky white PE-like degradable copolyester was obtained.
[0125] According to the test, the molar ratio of eicosanedioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 90:10, the residual amount of ethylene glycol is 0.4% which can be ignored; the intrinsic viscosity is 2.24dL / g; the number average molecular weight is 143000g / mol; according to the L*a*b* color model, the L* value is 82, the a* value is 3.3, and the b* value is 5.9; the glass transition temperature is -68.4℃, the melting point is 82.8℃; the tensile strength is 13.2MPa, the elongation at break is 820%; the water vapor permeability coefficient is 7.59×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 48%, the mass loss due to hydrolysis within 60 days was 32%, and the mass loss due to seawater degradation within 60 days was 7%.
[0126] Example 6
[0127] 0.123 mol of diethyl oxalate, 0.1722 mol of ethylene glycol and a composite catalyst of tetrabutyl titanate and antimony acetate with a mass fraction of 0.8‰ (based on diethyl oxalate) are put into a reactor, and the temperature is gradually raised to 160°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct ethanol collected is more than 95% of the theoretical value; the system is cooled to 120°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0128] 0.177 mol of dimethyl dodecanedioate, 0.31 mol of 1,12-dodecanediol and a composite catalyst of tetrabutyl titanate and antimony acetate with a mass fraction of 1‰ (based on dimethyl dodecanedioate) are put into a reactor, and the temperature is gradually raised to 185° C. under nitrogen protection to carry out a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 150° C., and the propylene glycol oxalate prepolymer prepared in the first step is added to carry out a third transesterification reaction, and the reaction is carried out for 1.5 hours;
[0129] The system was gradually heated to 200°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1 hour; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1 hour, and a milky white PE-like degradable copolyester was obtained.
[0130] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 60:40, the residual ethylene glycol content is 15%; the intrinsic viscosity is 1.44dL / g; the number average molecular weight is 119000g / mol; according to the L*a*b* color model, the L* value is 80, the a* value is 2.8, and the b* value is 5.7; the glass transition temperature is -64.8℃, the melting point is 89.2℃; the tensile strength is 13.5MPa, the elongation at break is 980%; the water vapor permeability coefficient is 5.11×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 64%, the mass loss due to hydrolysis within 60 days was 47%, and the mass loss due to seawater degradation within 60 days was 14%.
[0131] Example 7
[0132] 0.018 mol of dimethyl oxalate, 0.026 mol of butanediol and 0.8‰ (based on the mass fraction of dimethyl oxalate) of tetrabutyl titanate are put into a reactor, and the temperature is gradually raised to 180°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of methanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 150°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree butanediol oxalate prepolymer;
[0133] 0.282 mol of dimethyl docosane dioate, 0.32 mol of 1,22-docosanediol and tetrabutyl titanate with a mass fraction of 0.7‰ (accounting for dimethyl docosane dioate) are put into a reactor, and the temperature is gradually raised to 190° C. under nitrogen protection to carry out a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 150° C., and the oxalic acid butanediol prepolymer prepared in the first step is added to carry out a third transesterification reaction under the condition that the melt is completely melted, and the reaction is carried out for 1.5 hours;
[0134] The system was gradually heated to 210°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1.5h, and a milky white PE-like degradable copolyester was obtained.
[0135] According to the test, the molar ratio of docosane diacid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 94.4:5,6, the residual amount of ethylene glycol is 0.3% which can be ignored; the intrinsic viscosity is 2.44dL / g; the number average molecular weight is 167000g / mol; according to the L*a*b* color model, the L* value is 87, the a* value is 1.3, and the b* value is 3.5; the glass transition temperature is -69.8℃, the melting point is 80.5℃; the tensile strength is 11.9MPa, the elongation at break is 780%; the water vapor permeability coefficient is 4.33×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 47%, the mass loss due to hydrolysis within 60 days was 32%, and the mass loss due to seawater degradation within 60 days was 8%.
[0136] Example 8
[0137] 0.018 mol of diethyl oxalate, 0.024 mol of butanediol and 0.5‰ (based on the mass fraction of diethyl oxalate) of ethylene glycol antimony are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 1 hour, from the first drop of ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct ethanol collected is more than 95% of the theoretical value; the system is cooled to 120°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree butanediol oxalate prepolymer;
[0138] 0.282 mol of dimethyl tetracosanedioate, 0.32 mol of 1,24-tetracosandiol and a mixture of titanium isopropoxide and triethyl antimonate with a mass fraction of 1‰ (based on dimethyl tetracosanedioate) are put into a reactor, and the temperature is gradually raised to 190° C. under nitrogen protection to carry out a second esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol dripping is the timing zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 150° C., and the oxalic acid butanediol prepolymer prepared in the first step is added to carry out a third transesterification reaction under the condition that the melt is completely melted, and the reaction is carried out for 1 hour;
[0139] The system was gradually heated to 210°C and depressurized to 200Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 1 hour; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1 hour, and a milky white PE-like degradable copolyester was obtained.
[0140] According to the test, the molar ratio of tetracosanoic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 94:6, the residual amount of ethylene glycol is 0.3% which can be ignored; the intrinsic viscosity is 1.68dL / g; the number average molecular weight is 116000g / mol; according to the L*a*b* color model, the L* value is 82, the a* value is 2.4, and the b* value is 3.5; the glass transition temperature is -67.2℃, the melting point is 80.7℃; the tensile strength is 11.3MPa, the elongation at break is 670%; the water vapor permeability coefficient is 4.46×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 44%, the mass loss due to hydrolysis within 60 days was 30%, and the mass loss due to seawater degradation within 60 days was 6%.
[0141] Example 9
[0142] 0.063 mol of diethyl oxalate, 0.0504 mol of butanediol and 0.1‰ (based on the mass fraction of diethyl oxalate) of ethylene glycol antimony are put into a reactor, and the temperature is gradually raised to 140°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 4 hours, from the first drop of ethanol dripping as the timing zero point, to the end point of the esterification reaction or transesterification reaction when the amount of byproduct ethanol collected is more than 95% of the theoretical value; the system is cooled to 110°C, the reaction system is depressurized to 200 Pa, and the first pre-polycondensation reaction is carried out for 1 hour to obtain a low-polymerization degree butanediol oxalate prepolymer;
[0143] 0.237 mol of dimethyl 2-tetracosanedioate, 0.3 mol of 1,24-tetracosanedioic acid, and a mixture of titanium isopropoxide and triethyl antimonate with a mass fraction of 0.1‰ (accounting for dimethyl 2-tetracosanedioate) are put into a reactor, and the temperature is gradually raised to 170°C under nitrogen protection for a second esterification reaction or transesterification reaction, and the reaction is carried out for 1 hour. The time from the first drop of methanol dripping is the zero point, and the time from the collection of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 160°C, and a prepolymer of oxalic acid butanediol is added to carry out a third transesterification reaction under the condition that the melt is completely melted, and the reaction is carried out for 1 hour; wherein, the molar ratio of the sum of the molar amounts of dimethyl 2-tetracosanedioate and the prepolymer of oxalic acid butanediol to 1,24-tetracosanedioic acid is 1.2:1;
[0144] The system was gradually heated to 220°C and depressurized to 100Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 3h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1h, and a milky white PE-like degradable copolyester was obtained.
[0145] According to the test, the molar ratio of tetracosanoic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 80.2:19.8, the residual amount of ethylene glycol is 0.9% which can be ignored; the intrinsic viscosity is 1.77dL / g; the number average molecular weight is 132000g / mol; according to the L*a*b* color model, the L* value is 80, the a* value is 2.2, and the b* value is 3.1; the glass transition temperature is -62.8℃, the melting point is 83.5℃; the tensile strength is 12.5MPa, the elongation at break is 710%; the water vapor permeability coefficient is 4.21×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days is 40%, the mass loss due to hydrolysis within 60 days is 24%, and the mass loss due to seawater degradation within 60 days is 5%.
[0146] Example 10
[0147] 0.048 mol of dimethyl oxalate, 0.0624 mol of ethylene glycol and antimony acetate with a mass fraction of 3‰ (based on dimethyl oxalate) are put into a reactor, and the temperature is gradually raised to 140°C under nitrogen protection conditions, and the first esterification reaction or transesterification reaction is carried out for 3 hours, from the first drop of methanol or ethanol dripping to the time zero point, and the esterification reaction or transesterification reaction end point is when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 110°C, the reaction system is depressurized to 400Pa, and the first pre-polycondensation reaction is carried out for 4 hours to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0148] 0.252 mol of dimethyl eicosandioate, 0.3 mol of 1,20-eicosandioic acid, and triethyl antimonate with a mass fraction of 3‰ (accounting for dimethyl eicosandioate) were put into a reactor, and the temperature was gradually raised to 170°C under nitrogen protection for a second esterification reaction or transesterification reaction, and the reaction lasted for 4 hours. The time from the first drop of methanol dripping was the zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value was the end point of the esterification reaction or transesterification reaction; the system was cooled to 130°C, and ethylene glycol oxalate prepolymer was added to carry out a third transesterification reaction, and the reaction lasted for 2 hours; wherein, the molar ratio of the sum of the molar amounts of dimethyl eicosandioate and ethylene glycol oxalate prepolymer to 1,20-eicosandioic acid was 1.2:1;
[0149] The system was gradually heated to 240°C and depressurized to 500Pa for a second pre-polycondensation reaction, the second pre-polycondensation reaction time was 0.5h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 0.5h, and a milky white PE-like degradable copolyester was obtained.
[0150] According to the test, the molar ratio of docosane diacid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 85.5:14.5, the residual amount of ethylene glycol is 0.7% which can be ignored; the intrinsic viscosity is 1.68dL / g; the number average molecular weight is 121000g / mol; according to the L*a*b* color model, the L* value is 84, the a* value is 2.7, and the b* value is 3.4; the glass transition temperature is -65.7℃, the melting point is 82.9℃; the tensile strength is 12.3MPa, the elongation at break is 650%; the water vapor permeability coefficient is 4.47×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 42%, the mass loss due to hydrolysis within 60 days was 28%, and the mass loss due to seawater degradation within 60 days was 7%.
[0151] Comparative Example 1
[0152] 0.3 mol of dimethyl dodecanedioate, 0.3 mol of 1,12-dodecanediol and 0.3‰ of tetrabutyl titanate are put into a reactor, and the temperature is gradually raised to 180°C under nitrogen protection to carry out esterification reaction or transesterification reaction. The reaction is carried out for 3 hours, and the timing is zero from the first drop of methanol dripping, and the end point of the esterification reaction or transesterification reaction is when the amount of byproduct methanol collected is more than 95% of the theoretical value;
[0153] The system was gradually heated to 210°C and depressurized to 200Pa for a pre-polycondensation reaction, the pre-polycondensation reaction time was 1.5h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 1.5h, and a PE-like copolyester was obtained.
[0154] The test results show that the PE copolyester has clear structures of dodecanedioic acid and dodecanedioic acid; the intrinsic viscosity is 2.21dL / g; the number average molecular weight is 137000g / mol; according to the L*a*b* color model, the L* value is 88, the a* value is 3.5, and the b* value is 4.3; the glass transition temperature is -69.7℃, and the melting point is 84.7℃; the tensile strength is 11.7MPa, and the elongation at break is 1500%; the water vapor permeability coefficient is 9.48×10 -14 g cm / cm 2·s·Pa; the mass loss by enzyme degradation was 9% within 60 days, and there was no mass degradation by hydrolysis within 60 days.
[0155] Comparative Example 2
[0156] 0.063 mol of dimethyl oxalate, 0.237 mol of dimethyl dodecanedioate, 0.32 mol of 1,12-dodecanediol and 0.6‰ of tetrabutyl titanate are added into the reactor, and the temperature is gradually raised to 160°C under nitrogen protection, and the reaction is carried out for 3 hours. The time zero is the time when the first drop of methanol drips, and the end point of the esterification reaction or the transesterification reaction is when the amount of byproduct methanol collected is more than 95% of the theoretical value;
[0157] The system was gradually heated to 200°C and the pressure was reduced to 20 Pa for pre-polycondensation reaction. A large amount of white solid precipitated in the collection bottle, the melt could not solidify and agglomerate, no torque was generated, and the melt turned black.
[0158] Comparative Example 3
[0159] 0.063 mol of dimethyl oxalate, 0.237 mol of dimethyl dodecanedioate, 0.088 mol of ethylene glycol, 0.32 mol of 1,12-dodecanediol and a composite catalyst of tetrabutyl titanate and titanium isopropoxide with a mass fraction of 0.8‰ were put into a reactor, and the temperature was gradually raised to 160°C under nitrogen protection conditions, and the reaction was carried out for 4 hours, with the first drop of methanol dripping as the timing zero point, and the amount of byproduct methanol collected reaching 70% of the theoretical value and unable to increase further;
[0160] The system was gradually heated to 200°C and depressurized to 200Pa for a pre-polycondensation reaction, the pre-polycondensation reaction time was 2h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 8h, and a yellow PE copolyester was obtained.
[0161] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE copolyester is 91.4:8.6, the residual ethylene glycol content is 6.4%, the intrinsic viscosity is 0.35 dL / g, and the number average molecular weight is 18000 g / mol.
[0162] Comparative Example 4
[0163] 0.15 mol of dimethyl oxalate, 0.21 mol of ethylene glycol and 2‰ of titanium isopropoxide are put into a reactor, and the temperature is gradually raised to 150°C under nitrogen protection conditions, and the reaction is carried out for 1.5 hours. The time is zero when the first drop of methanol drips, and the end point of the esterification reaction or transesterification reaction is when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 120°C, the reaction system is depressurized to 200 Pa, and the reaction is carried out for 1 hour to obtain a low-polymerization degree oxalic acid ethylene glycol ester prepolymer;
[0164] 0.15 mol of dimethyl dodecanedioate, 0.3 mol of 1,12-dodecanediol and 0.8‰ of tetrabutyl titanate are put into a reactor, and under the protection of nitrogen, the temperature is gradually raised to 180°C for esterification reaction or transesterification reaction, and the reaction is carried out for 2 hours. The time from the first drop of methanol dripping is the zero point, and the time from the collection amount of byproduct methanol to more than 95% of the theoretical value is the end point of the esterification reaction or transesterification reaction; the system is cooled to 150°C, and ethylene glycol oxalate prepolymer is added to carry out transesterification reaction, and the reaction is carried out for 4 hours;
[0165] The system was gradually heated to 210°C and depressurized to 200Pa for a pre-polycondensation reaction, the pre-polycondensation reaction time was 2h; the reaction system was further depressurized to less than 20Pa for a final polycondensation reaction, the final polycondensation reaction had a stable vacuum degree of less than or equal to 7Pa, the final polycondensation reaction time was 4h, and a yellow PE copolyester was obtained.
[0166] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE copolyester is 54:46, the residual ethylene glycol content is 24.8%; the intrinsic viscosity is 1.32dL / g; the number average molecular weight is 107000g / mol; according to the L*a*b* color model, the L* value is 75, the a* value is 5.4, and the b* value is 8.9; the glass transition temperature is -64.5℃, the melting point is 78.8℃; the tensile strength is 10.1MPa, the elongation at break is 350%; the water vapor permeability coefficient is 15.3×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 84%, the mass loss due to hydrolysis within 60 days was 67%, and the mass loss due to seawater degradation within 60 days was 35%.
[0167] Comparative Example 5
[0168] 0.063 mol dimethyl oxalate, 0.088 mol ethylene glycol, 0.32 mol 1,12-dodecanediol and a mixed catalyst of 0.5‰ titanium isopropoxide and 1‰ tetrabutyl titanate are put into a reactor, and under nitrogen protection, the temperature is gradually raised to 150°C for a first esterification reaction or transesterification reaction for 1 hour, and the temperature is gradually raised to 180°C for a second esterification reaction or transesterification reaction for 2 hours, from the first drop of methanol dripping as the timing zero point to the end of the esterification reaction or transesterification reaction when the amount of byproduct methanol collected is more than 95% of the theoretical value; the system is cooled to 150°C, the reaction system is depressurized to 200Pa, and the first pre-polycondensation reaction is carried out for 1 hour; the system is gradually heated to 210°C, the pressure is reduced to 200Pa for a second pre-polycondensation reaction, and the second pre-polycondensation reaction time is 1 hour; the reaction system is further depressurized to less than 20Pa for a final polycondensation, the stable vacuum degree of the final polycondensation reaction is less than or equal to 7Pa, and the final polycondensation time is 2 hours, to obtain a PE-like degradable copolyester.
[0169] After testing, this type of PE degradable copolyester is a homopolyester of dodecanediol oxalate, with a negligible 0.9% ethylene glycol residue; an intrinsic viscosity of 1.55 dL / g; a number average molecular weight of 110000 g / mol; according to the L*a*b* color model, the L* value is 89, the a* value is 2.9, and the b* value is 5.8; the glass transition temperature is -54.6°C, and the melting point is 128.6°C; the tensile strength is 18.2 MPa, and the elongation at break is 500%; the water vapor permeability coefficient is 6.33×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 85%, the mass loss due to hydrolysis within 60 days was 57%, and the mass loss due to seawater degradation within 60 days was 21%.
[0170] Comparative Example 6
[0171] 0.063 mol of dimethyl oxalate, 0.237 mol of dimethyl dodecanedioate, 0.42 mol of ethylene glycol and a mixed catalyst of 0.5‰ titanium isopropoxide and 1‰ tetrabutyl titanate were put into the reactor. Under nitrogen protection, the temperature was gradually raised to 150°C for the first esterification reaction or transesterification reaction for 1 hour, and the temperature was gradually raised to 180°C for the second esterification reaction or transesterification reaction for 2.5 hours. The timer was set from the first drop of methanol dripping to the amount of byproduct methanol collected. More than 95% of the theoretical value is the end point of the esterification reaction or the ester exchange reaction; the system is cooled to 150°C, the reaction system is depressurized to 200Pa, and the first pre-polycondensation reaction is carried out for 1 hour; the system is gradually heated to 190°C, and the pressure is reduced to 200Pa for a second pre-polycondensation reaction, and the second pre-polycondensation reaction time is 1 hour; the reaction system is further depressurized to less than 20Pa for the final polycondensation, the stable vacuum degree of the final polycondensation reaction is less than or equal to 7Pa, and the final polycondensation time is 2 hours, to obtain a PE-like degradable copolyester.
[0172] According to the test, the molar ratio of dodecanedioic acid to oxalic acid in the dibasic acid composition of this type of PE degradable copolyester is 85.3:14.7; the intrinsic viscosity is 1.12dL / g; the number average molecular weight is 87000g / mol; according to the L*a*b* color model, the L* value is 83, the a* value is 2.1, and the b* value is 5.4; the glass transition temperature is -48.4℃, the melting point is 135.8℃; the tensile strength is 17.4MPa, the elongation at break is 400%; the water vapor permeability coefficient is 6.18×10 -14 g cm / cm 2 ·s·Pa; the mass loss due to enzyme degradation within 60 days was 87%, the mass loss due to hydrolysis within 60 days was 63%, and the mass loss due to seawater degradation within 60 days was 24%.
[0173] It can be seen from Example 1 and Comparative Example 1 that the PE-like polyester without oxalic acid segments on the molecular chain will hardly degrade; it can be seen from Example 1, Comparative Example 2 and Comparative Example 3 that when diethyl oxalate or diethyl oxalate and ethylene glycol are directly reacted with long-chain dibasic acid by a one-pot method, the oxalic acid segments are thermally degraded in the polycondensation stage due to insufficient esterification, and the long-chain diol in the system cannot be extracted, resulting in the inability to increase the molecular weight, and the PE-like polyester turns yellow and black, and even cannot be synthesized; it can be seen from Example 1 and Comparative Example 4 that when the oxalic acid glycol prepolymer exceeds 20% in the long-chain dibasic acid system, Even if the transesterification reaction time is sufficient, ethylene glycol cannot be completely extracted from the reaction system during polycondensation, resulting in too high ethylene glycol content in the molecular chain, changes in the PE-like polyester structure, and uncontrollable molecular structure; from Example 1 and Comparative Example 5, it can be seen that without adding dimethyl dodecanedioate to obtain dodecanedioic acid dodecanedioic acid ester homopolymer, ethylene glycol can also be completely extracted, and the content is negligible; from Example 1 and Comparative Example 6, it can be seen that without adding 1,12-dodecanediol, even if the polycondensation temperature is lowered, part of ethylene glycol and oxalic acid are extracted from the system, and the product ratio is uncontrollable.
[0174] Through the above technical scheme, the present invention can effectively synthesize high molecular weight PE-like degradable copolyester through condensation polymerization by coordinating the length of the methylene group in the polyester structure and the content of the oxalic acid unit, thereby ensuring that the PE-like degradable copolyester has good and stable thermal properties, mechanical properties and barrier properties, while being able to regulate the degradation rate of the copolyester.
[0175] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0176] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A polyethylene-like degradable copolyester, characterized in that: The structural formula of the polyethylene-like degradable copolyester is shown in formula (1): Wherein, -R1- is a structural unit of a long-chain dibasic acid or its ester, -O-R2-O- is a structural unit of a long-chain diol, m, n, and x are all integers, m=1 to 10, n=1 to 10, and x=10 to 100; and -R1- and The molar ratio is 3:2 to 19:
1.
2. The polyethylene-like degradable copolyester according to claim 1, characterized in that: -R1-with The molar ratio is 3:2 to 19:1; And / or, the structural unit of the long-chain dibasic acid or its ester is selected from at least one of the structures shown in formula (2): Wherein, a is an integer, a=10 to 23; And / or, the long-chain diol is selected from at least one of the structures shown in formula (3): Wherein, c is an integer, c=12~25.
3. The polyethylene-like degradable copolyester according to claim 1, characterized in that: The polyethylene-like degradable copolyester has an intrinsic viscosity of 1.5 to 2.5 dL / g and a number average molecular weight of 80,000 to 160,000 g / mol; according to the L*a*b* color model, the L* value is greater than 80, the a* absolute value is less than 4, and the b* absolute value is less than 8; And / or, the polyethylene-like degradable copolyester has a glass transition temperature of -80 to 65°C, a melting point of 70 to 105°C, a tensile strength of 10 to 40 MPa, an elongation at break of 600 to 1600%, and a water vapor permeability of 4×10 -14 ~10×10 -14 g cm / cm 2 ·s·Pa, the mass loss after 60 days of hydrolysis is 30-50%, the mass loss after 60 days of enzyme degradation is 40-70%, and the mass loss after 60 days of seawater degradation is 5-15%.
4. A method for preparing a polyethylene-like degradable copolyester, characterized in that: include: Mixing dimethyl oxalate and / or diethyl oxalate, a first diol, and an esterification catalyst to form a first mixed system, and subjecting the first mixed system to a first esterification reaction or a first transesterification reaction to obtain a first esterification product or a first transesterification product; Then the temperature is lowered to carry out a first pre-polycondensation reaction to obtain an oxalic acid prepolymer with a low degree of polymerization; Mixing a long-chain dibasic acid or an esterified product thereof, a long-chain diol, and an esterification catalyst to form a second mixed system, and subjecting the second mixed system to a second esterification reaction or a second transesterification reaction to obtain a second esterification product or a second transesterification product; The oxalic acid prepolymer, the second esterification product or the second ester exchange product are mixed to form a third mixed system, and the third mixed system is subjected to a third ester exchange reaction under the condition that the melt is completely melted, and then the temperature is increased to carry out a second pre-polycondensation reaction and a final polycondensation reaction to obtain a polyethylene-like degradable copolyester.
5. The preparation method according to claim 4, characterized in that: The first diol includes at least one of ethylene glycol, propylene glycol, and butylene glycol; and / or, the molar ratio of the dimethyl oxalate and / or diethyl oxalate to the first diol is 1:1.2 to 1:1.5; and / or, the temperature of the first esterification reaction or the first transesterification reaction is 140-180° C. and the time is 1-4 h; And / or, the preparation method comprises: after the first esterification reaction or the first transesterification reaction is completed, the temperature is reduced to 100-150° C., and the pressure of the reaction system is reduced to 200-1000 Pa to carry out a first pre-polycondensation reaction for 0.5-4 hours to obtain an oxalic acid prepolymer with a low degree of polymerization; And / or, the oxalic acid prepolymer has at least one of the structures shown in formula (4): Among them, the diol from which -O-R3-O- is derived is selected from at least one of ethylene glycol, propylene glycol, and butanediol; b is an integer, b=1-10.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the sum of the molar amount of the long-chain dibasic acid or the long-chain dibasic acid ester and the molar amount of the oxalate structure in the oxalic acid prepolymer to the long-chain diol is 1:1 to 1.2:1; And / or, the structural unit of the long-chain dibasic acid or its ester is selected from at least one of the structures shown in formula (2): Wherein, a is an integer, a=10 to 23; And / or, the long-chain diol is selected from at least one of the structures shown in formula (3): Wherein, c is an integer, c=12 to 25; and / or, the temperature of the second esterification reaction or the second transesterification reaction is 170-210° C. and the time is 1-4 hours; And / or, the esterification catalyst includes at least one of an antimony-based catalyst and a titanium-based catalyst; and / or, in the first mixed system, the mass of the esterification catalyst accounts for 0.1‰ to 3‰ of the mass of dimethyl oxalate and / or diethyl oxalate; And / or, in the second mixed system, the mass of the esterification catalyst accounts for 0.1‰ to 3‰ of the mass of the long-chain dibasic acid or its esterification product.
7. The preparation method according to claim 6, characterized in that: The temperature of the first esterification reaction or the first transesterification reaction is 140 to 160° C.; And / or, the preparation method comprises: after the first esterification reaction or the first transesterification reaction is completed, the temperature is reduced to 110-130° C., and the pressure of the reaction system is reduced to 200-400 Pa to carry out a first pre-polycondensation reaction for 1-1.5 hours to obtain an oxalic acid prepolymer with a low degree of polymerization; and / or, the temperature of the second esterification reaction or the second transesterification reaction is 170-190° C.; and / or, the temperature of the third transesterification reaction is 130-160° C. and the time is 0.5-2 h; And / or, the antimony-based catalyst includes any one or a combination of two or more of antimony trioxide, antimony acetate, ethylene glycol antimony, and triethyl antimonate; And / or, the titanium-based catalyst includes any one or a combination of two or more of titanium isopropoxide, tetrabutyl titanate, and tetraethyl titanate; And / or, in the first mixed system, the mass of the esterification catalyst accounts for 0.5‰ to 1‰ of the mass of dimethyl oxalate and / or diethyl oxalate: and / or, in the second mixed system, the mass of the esterification catalyst accounts for 0.5‰ to 1‰ of the mass of the long-chain dibasic acid or its esterified substance; And / or, the preparation method comprises: gradually heating the reaction system obtained by the third ester exchange reaction to 190-240°C, reducing the pressure of the reaction system to 100-500Pa for a second pre-polycondensation reaction, the time of the second pre-polycondensation reaction being 0.5-3h; then reducing the pressure of the reaction system to less than 20Pa, carrying out a final polycondensation reaction, the stable vacuum degree of the polycondensation reaction not exceeding 7Pa, the time of the polycondensation reaction being 0.5-2h, to obtain the polyethylene-like degradable copolyester.
8. The preparation method according to claim 7, characterized in that: The temperature of the third transesterification reaction is 140-150° C. and the time is 1-1.5 h; And / or, the preparation method comprises: gradually heating the reaction system obtained by the third ester exchange reaction to 200-220°C, reducing the pressure of the reaction system to 200-400Pa for a second pre-polycondensation reaction, the time of the second pre-polycondensation reaction being 1-1.5h; then reducing the pressure of the reaction system to less than 20Pa, carrying out a final polycondensation reaction, the stable vacuum degree of the polycondensation reaction not exceeding 7Pa, the time of the polycondensation reaction being 1-2h, to obtain the polyethylene-like degradable copolyester.
9. The polyethylene-like degradable copolyester prepared by the preparation method according to any one of claims 4 to 8.
10. Use of the polyethylene-like degradable copolyester according to any one of claims 1 to 3 and 9 in the preparation of agricultural mulch films, fiber fabrics, telecommunication cables, packaging materials, plastic container products, tissue engineering scaffolds or drug carriers.
Citation Information
Patent Citations
Preparation method of polyethylene terephthalate-ethylene glycol copolyester
CN102276808A
Biodegradable alternative aliphatic polyester amide and preparation method thereof
CN111349233A
Preparation method of high-molecular-weight poly(hexanediol oxalate)
CN113527644A
Polyester and producing method thereof
JP2014012797A